2013
DOI: 10.5539/ijbm.v8n15p112
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Specific Forensic Accounting Conceptual Framework: A Skills Set Theoretical Analysis

Abstract: Forensic accounting, given its peculiar investigative stance, requires a specific skills set on the part of the forensic accountant, that integrates accounting, auditing and investigative skills. The Jordanian Anti-Corruption Commission's (JACC) struggle to investigate Maward's, a Jordanian state-own company, suspected corruption has raised serious concerns regarding the weak state of forensic accounting in Jordan, and the need for its adaptation to suit the country's peculiar context, to successfully institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The concept of forensic accounting field is new, resulting in a scarcity of studies. Nevertheless, as argued by Harris (2012) and Shanikat and Khan (2013), there is a continuous demand in all sectors for accountants who work in the framework of forensic accounting. In the same vein, the survey done by McMullen and Sanchez (2010) found that the forensic accountants' demand might be increased in the upcoming future, especially in fraudulent financial reporting area.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of forensic accounting field is new, resulting in a scarcity of studies. Nevertheless, as argued by Harris (2012) and Shanikat and Khan (2013), there is a continuous demand in all sectors for accountants who work in the framework of forensic accounting. In the same vein, the survey done by McMullen and Sanchez (2010) found that the forensic accountants' demand might be increased in the upcoming future, especially in fraudulent financial reporting area.…”
Section: Introductionmentioning
confidence: 99%
“…The growing need for forensic accounting experts has necessitated the adoption of a formal approach to forensic accounting education (Seda and Kramer, 2014; Matson, 2016). The curriculum for forensic accounting education must be comprehensive (West Virginia University, 2007; Shanikat and Khan, 2013; Lang et al , 2014; Clements and Knudstrup, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fraudsters influence and manipulate the employees by applying the human skills. A forensic accountant should have good command over the subjects like criminology and psychology (Shanikat and Khan, 2013). Knowledge of sociology is essential for detecting the clues leading to commitment of fraud, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the aftermath of the recent global financial scandals, there has been a negative perception of auditors' independence, and of the effectiveness of traditional audit procedures to protect users from fraudulent financial reporting (Hao, 2010;Huber, 2012). Shanikat and Khan (2013) emphasise the growing need for professional accountants to understand the area of financial statement fraud, while Siegel and Shim (2010) identify the need for accountants who have deeper understanding of fraud as forensic accountants.…”
Section: Context Of Researchmentioning
confidence: 99%
“…Despite the growing need for accountants with forensic accounting skills, limited background information exists with respect to forensic accounting education in the context of developing countries and in particular relating to Jordan (Elitas et al, 2011;Shanikat and Khan, 2013;Alabdullah et al, 2014). The way in which accounting practices are taught in developing countries, and the solutions to their unique problems, requires a different approach when compared to Western countries.…”
Section: Context Of Researchmentioning
confidence: 99%